PEMIKIRAN KH. THOLHAH HASAN DAN BJ. HABIBIE TENTANG PENDIDIKAN ISLAM - Ahmad Syukri Billah Ghazali; Moh Murtado; Ibnu ` Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Islamic education is an effort of physical and spiritual guidance at the level of individual and social life to develop human nature based on Islamic laws towards the formation of an ideal human being (insan kamil) who has a Muslim personality and is commendable and obedient to Islam so as to achieve happiness in the world and the hereafter. Nowadays more and more prominent figures or experts have contributed or contributed to the development or formation of Islamic education and all its aspects. Their services through their work or ideas are not insignificant in the context of contributing to changes in the Indonesian human condition. His contribution is in accordance with the disciplines he has and masters. 1. How KH. Tholhah Hasan and BJ Habibie, what contributions have KH.Tholhah Hasan and BJ made. Habibi gave 2. The research method in this writing uses a descriptive method (decriptive method), which clearly explains some of the problems that are revealed through the literature approach. or dig up data sourced from reading material, and various literature that examines the problem of Islamic education and career path KH. Tholhah Hasan and BJ. Habibie.Kata Kunci: Pemikiran, Pendidikan, Islam.